ANALYSIS AND EVALUATION OF FINANCIAL MANAGEMENT STRATEGIES OF SPORTS CLUBS - Alexandru Simion (Annals of the University of Craiova: Economic Sciences Series, 2022)
In order to be successful in an increasingly competitive environment, today every sports organization has to face challenges, which are increasingly difficult to anticipate with accuracy, a fact that causes management to care more and more about performance. The strategic approach to the management of a sports organization has as its starting point the fact that sport has become, in the current era, a complex phenomenon with economic, political and social connotations. We have focused the study on the analysis of financial management strategies and practices used by top sports clubs in Europe, as this is where the highest turnover is obtained in the field of football, highlighting the factors that led to the advantages or disadvantages of applying such strategie.